2007
DOI: 10.1308/003588407x168352
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Comparison of Handover Methods

Abstract: Ann R Coll Surg Engl 2007; 89: 298-300 298Medical handover is 'the transfer of professional responsibility and accountability for some or all aspects of care for a patient, or group of patients, to another person or professional group on a temporary or permanent basis'.1 The implementation of the New Deal and the European Working Time Directive has meant that junior doctors are increasingly working in shifts and that handover of clinical information is taking place more frequently. There is reduced continuity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
104
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(109 citation statements)
references
References 1 publication
2
104
0
1
Order By: Relevance
“…9 Bhabra et al have shown, using simulated patient handovers, that verbalonly handover leads to considerable loss of information compared to verbal handover with written notes. 10 When information loss was analysed, important and less important information in patient handover were lost at a similar rate. Ferran et al studied the use of standardised proformas to improve patient handover, auditing information handover for trauma patients before and after the introduction of a proforma.…”
Section: Discussionmentioning
confidence: 99%
“…9 Bhabra et al have shown, using simulated patient handovers, that verbalonly handover leads to considerable loss of information compared to verbal handover with written notes. 10 When information loss was analysed, important and less important information in patient handover were lost at a similar rate. Ferran et al studied the use of standardised proformas to improve patient handover, auditing information handover for trauma patients before and after the introduction of a proforma.…”
Section: Discussionmentioning
confidence: 99%
“…A verbal report has the potential weakness of poor retention of information by the receiver, and there may be discrepancies between the reported status and the actual patient status because of memory failure on the part of the reporter (Frankel, 2012). Literature shows that after five handover cycles, only 2.5% of patient information was retained using the verbal-only handover method while 85.5% was retained when using the verbal with note taking method and 99% was retained when a printed handout containing all patient information was used (Bhabra et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A structured pre-printed form, a new method for collecting and recalling data during the shift-to-shift handoff was chosen because it had already been shown in literature to be the most effective [13,15,16] . This method is supported by studies that encourage the use of a consistent pre-printed forms with relevant patient information during shift report, with less reliance on verbal-only reports, in order to optimize communication.…”
Section: Discussionmentioning
confidence: 99%